Circular depolarization spectroscopy: A new tool to study photo‐imprinting of chirality. Issue 3 (13th January 2023) - Kulkarni, Chidambar; Sakaino, Hirotoshi; Vantomme, Ghislaine; Meskers, Stefan C. J.
Abstract: When irradiating a molecular material containing photo‐isomerizable groups with pure circularly polarized light, a particular handedness may get imprinted into the material. To study the mechanism and kinetics of this process in situ and operando, we have developed a new chiroptical tool where the circular polarization of the incident circularly polarized light is monitored after transmission through the photoactive layer. Practical limits to the resolution and sensitivity of the measurements as well as its calibration are discussed. To aid interpretation of experimental results, we present kinetic Monte Carlo simulations on a model for the active material involving photo‐induced reorientation of molecules in a cholesteric organization. The simulations support the interpretation of a transient minimum in the degree of circular polarization of the transmitted light in terms of a nematic transient state during photo‐inversion of a cholesteric organization in the molecular material. Abstract : Circular depolarization is a new spectrosopic tool to study photo‐imprinting of chirality in films of photo‐isomerizable polymer in situ and operando .